Gutmann’s Donor and Acceptor Numbers for Ionic Liquids and Deep Eutectic Solvents - Sanchez, Bruno; Campodónico, Paola R.; Contreras, Renato (Frontiers in Chemistry, 2022)
An experimental and computational methodology for the analysis of the Lewis acid/base responses of ionic liquids (ILs) and deep eutectic solvents (DES) is proposed. It is based on the donor and acceptor of the electronic charge ability of Lewis acid and bases concepts (donicity and acceptor numbers, DN and AN, respectively) proposed by Viktor Gutmann. The binding enthalpy between the IL/DES with the probe antimony pentachloride (SbCl5) in dichloroethane displays good correlations with experimental data. This approach could serve as a first approximation to predict the responses to H-bonding abilities of new IL or DES. Although useful, the problems encountered to model the electron AN of these solvents limit the usefulness of the approach to completely describe their polarity properties. The experimental data were recorded using UV–Vis spectroscopy for a wide range of ILs and a couple of DES. Two reactions were used as benchmarks to test the reliability of the DN model to discuss the reactivity of real systems in these neoteric solvents.